THE STAGES OF ENGLISH LANGUAGE ACQUISITION: A COMPREHENSIVE ANALYSIS OF LEARNING PROFICIENCY - Tojiyeva Marxabo Akbarovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the systematic progression of English language learning, categorized into distinct development stages. Based on contemporary cognitive linguistics and Second Language Acquisition (SLA) theories, the study evaluates how learners transition from total beginners to fluent, proficient speakers. The analysis investigates the phonetic, morphological, and syntactic adjustments that occur at each level—ranging from pre-production to advanced fluency. Additionally, it highlights key psychological factors, pedagogical practices, and environmental conditions that optimize transition rates between these stages. This framework serves as a guide for curriculum designers and educators to implement scaffolded teaching methods adjusted to learners’ developmental needs.